Neutrophils suppress γδ T-cell function - Sabbione, Florencia (2013)
γδ T cells have been shown to stimulate the recruitment and activation of neutrophils through the release of a range of cytokines and chemokines. Here, we investigated the reverse relationship, showing that human neutrophils suppress the function of human blood γδ T cells. We show that the upregulation of CD25 and CD69 expression, the production of IFN-γ, and the proliferation of γδ T cells induced by (E)-1-hydroxy-2-methylbut-2-enyl 4-diphosphate are inhibited by neutrophils. Spontaneous activation of γδ T cells in culture is also suppressed by neutrophils. We show that inhibitors of prostaglandin E2 and arginase I do not exert any effect, although, in contrast, catalase prevents the suppression of γδ T cells induced by neutrophils, suggesting the participation of neutrophil-derived ROS. We also show that the ROS-generating system xanthine/xanthine oxidase suppresses γδ T cells in a similar fashion to neutrophils, while neutrophils from chronic granulomatous disease patients only weakly inhibit γδ T cells. Our results reveal a bi-directional cross-talk between γδ T cells and neutrophils: while γδ T cells promote the recruitment and the activation of neutrophils to fight invading pathogens, neutrophils in turn suppress the activation of γδ T cells to contribute to the resolution of inflammation.